The way back home - Jeffers, Oliver (London : HarperCollins, 2007)
Stranded on the moon after his extraordinary airplane takes him into outer space, a boy meets a marooned young Martian with a broken spacecraft, and the two new friends work together to return to their respective homes.
2.0
K-3
Keywords: Cooperativeness -- Juvenile fiction; Space flight -- Juvenile fiction; Cooperativeness -- Fiction; Extraterrestrial beings -- Fiction; Space flight -- Fiction; Cooperativeness -- Fiction; Extraterrestrial beings -- Fiction; Science fiction; Moon -- Juvenile fiction; Moon -- Fiction; Moon -- Fiction